1977
DOI: 10.1021/bi00624a008
|View full text |Cite
|
Sign up to set email alerts
|

Actin and myosin-linked calcium regulation in the nematode Caenorhabditis elegans. Biochemical and structural properties of native filaments and purified proteins

Abstract: Calcium regulation of actomyosin activity in the nematode, Caenorhabditis elegans, has been studied with purified proteins and crude thin filaments. Actin and tropomyosin have been purified from C. elegans and shown to be similar in most respects to actin and tropomyosin from rabbit skeletal muscle. The actin comigrates with rabbit actin on polyacrylamide-sodium dodecyl sulfate gel electrophoresis, forms similar filaments and paracrystals, and activates the Mg2+-ATPase of rabbit myosin heads as efficiently as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…The predicted size of Ov-TMY-1 from sequence data is 33.2 kDa, suggesting that it may be posttranslationally modified. However, several tropomyosins have been recorded as migrating anomalously on SDS͞PAGE gels, including those of C. elegans (37), Ascaris lumbricoides (38), and T. colubriformis (14). In the case of T. colubriformis, glycanase treatment of native tropomyosin indicated that it was not modified with sugars (14).…”
Section: Resultsmentioning
confidence: 99%
“…The predicted size of Ov-TMY-1 from sequence data is 33.2 kDa, suggesting that it may be posttranslationally modified. However, several tropomyosins have been recorded as migrating anomalously on SDS͞PAGE gels, including those of C. elegans (37), Ascaris lumbricoides (38), and T. colubriformis (14). In the case of T. colubriformis, glycanase treatment of native tropomyosin indicated that it was not modified with sugars (14).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is possible that the activity of myosin is regulated by a separate mechanism, which may prevent hypercontraction when the TM-TN system is inhibited. Indeed, biochemical studies on isolated C. elegans myosin and actin demonstrated that C. elegans has both actin-and myosinlinked regulatory systems for the actomyosin activity (Harris et al, 1977). Regulatory myosin light chains often play critical roles in the regulation of myosin activity, although the regulatory mechanisms are various.…”
Section: Discussionmentioning
confidence: 99%
“…The regulatory MLCs of skeletal and cardiac muscle are phosphorylated, but this appears to play a minor, modulatory role in the contractile cycle (35,50). The muscles of many invertebrates, including C. elegans, exhibit elements of both myosin-based and actin-based control (23,36). Genetic manipulation of MLC proteins will likely be required for a complete understanding of their in vivo * Corresponding author.…”
mentioning
confidence: 99%